High quality genome assembly of the amitochondriate eukaryote Monocercomonoides exilis - Treitli, Sebastian Cristian; Peña-Diaz, Priscila; Hałakuc, Paweł; Karnkowska, Anna; Hampl, Vladimír (Microbial genomics, 2021)
Monocercomonoides exilis is considered the first known eukaryote to completely lack mitochondria. This conclusion is based primarily on a genomic and transcriptomic study which failed to identify any mitochondrial hallmark proteins. However, the available genome assembly has limited contiguity and around 1.5 % of the genome sequence is represented by unknown bases. To improve the contiguity, we re-sequenced the genome and transcriptome of M. exilis using Oxford Nanopore Technology (ONT). The resulting draft genome is assembled in 101 contigs with an N50 value of 1.38 Mbp, almost 20 times higher than the previously published assembly. Using a newly generated ONT transcriptome, we further improve the gene prediction and add high quality untranslated region (UTR) annotations, in which we identify two putative polyadenylation signals present in the 3'UTR regions and characterise the Kozak sequence in the 5'UTR regions. All these improvements are reflected by higher BUSCO genome completeness values. Regardless of an overall more complete genome assembly without missing bases and a better gene prediction, we still failed to identify any mitochondrial hallmark genes, thus further supporting the hypothesis on the absence of mitochondrion.
Keywords: protozoální proteiny; nanopórové sekvenování; Whole Genome Sequencing; High-Throughput Nucleotide Sequencing; Protozoan Proteins; nanopore; Nanopore Sequencing; Genome Size; genome; Oxymonadida; délka genomu; stanovení celkové genové exprese; zastoupení bazí; regulace genové exprese; anotace sekvence; sekvenování celého genomu; vysoce účinné nukleotidové sekvenování; Base Composition; amitochondriate; Molecular Sequence Annotation; Gene Expression Regulation; Monocercomonoides; Gene Expression Profiling